How early studies on secreted and membrane protein quality control gave rise to the ER associated degradation (ERAD) pathway: The early history of ERAD - Needham, Patrick G.; Brodsky, Jeffrey L. (Biochimica et biophysica acta, 2013)
All newly synthesized proteins are subject to quality control check-points, which prevent aberrant polypeptides from harming the cell. For proteins that ultimately reside in the cytoplasm, components that also reside in the cytoplasm were known for many years to mediate quality control. Early biochemical and genetic data indicated that misfolded proteins were selected by molecular chaperones and then targeted to the proteasome (in eukaryotes) or to proteasome-like particles (in bacteria) for degradation. What was less clear was how secreted and integral membrane proteins, which in eukaryotes enter the endoplasmic reticulum (ER), were subject to quality control decisions. In this review, we highlight early studies that ultimately led to the discovery that secreted and integral membrane proteins also utilize several components that constitute the cytoplasmic quality control machinery. This component of the cellular quality control pathway is known as ER associated degradation, or ERAD. This article is part of a Special Issue entitled: Functional and structural diversity of endoplasmic reticulum. •Proteins in the secretory pathway are subject to quality control “decisions”.•It was thought that only the lysosome mediated secretory protein quality control.•These proteins are instead subject to degradation by the proteasome.•This pathway is known as ER associated degradation, or ERAD.